2020
DOI: 10.1016/j.ejogrb.2020.09.036
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin non-response in pregnant women at increased risk of pre-eclampsia

Abstract: All authors declare no interests that may have influenced the submitted work. EliTech has provided VerifyNow consumables for 100 patients. EliTech has not been involved in the design, conduct, management of the study, analysis or interpretation of the data, or the preparation, review or approval of this manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
(41 reference statements)
0
1
1
1
Order By: Relevance
“…In two more recent studies conducted in the UK, the prevalences of ASA non-response reported in the second trimester of pregnancy were 14.7% and 36% respectively. Their results differ from ours due to the methods used to measure ASA non-response, which were serum thromboxane B2 assay for Vinogradov et al in 2021 [9] and urinary 11-dehydrothromboxane B2 assay for Navaratnam et al in 2017 in the second study [10]. Indeed, the assay methods used by the latter in the detection of non-response to ASA more specifically identify the phase of primary hemostasis not inhibited by ASA, notably that of platelet activation [11,12].…”
Section: Discussioncontrasting
confidence: 55%
“…In two more recent studies conducted in the UK, the prevalences of ASA non-response reported in the second trimester of pregnancy were 14.7% and 36% respectively. Their results differ from ours due to the methods used to measure ASA non-response, which were serum thromboxane B2 assay for Vinogradov et al in 2021 [9] and urinary 11-dehydrothromboxane B2 assay for Navaratnam et al in 2017 in the second study [10]. Indeed, the assay methods used by the latter in the detection of non-response to ASA more specifically identify the phase of primary hemostasis not inhibited by ASA, notably that of platelet activation [11,12].…”
Section: Discussioncontrasting
confidence: 55%
“…Van Montfort (2020) [6], cho thấy rằng việc không tuân thủ aspirin trong quá trình chăm sóc lâm sàng có thể lên tới 75% ở những phụ nữ có nguy cơ cao tiền sản giật. Ở nhóm phụ nữ mang thai có nguy cơ cao tiền sản giật, việc không tuân thủ điều trị Aspirin có thể tác động lớn đến sự thay đổi của đáp ứng điều trị dự phòng tiền sản giật [4]. [5], phân tích thử nghiệm ASPRE dùng 150 mg aspirin để ngăn ngừa tiền sản giật, kết quả ghi nhận tỷ lệ đạt hiệu quả điều trị dự phòng tiền sản giật ở nhóm tuân thủ điều trị <90% chỉ đạt 40%; trong khi đó, nhóm >90% đạt 75% hiệu quả điều trị dự phòng.…”
Section: Tỷ Lệ Tuân Thủ đIều Trị Dự Phòng Tiền Sản Giậtunclassified
“…In the group of pregnant women at increased risk of PE, non-adherence to aspirin may play a pivotal role in the variability of response to treatment (Vinogradov et al, 2020). A recent subgroup analysis of the ASPRE trial (a randomised controlled trial (RCT) of 150 mg of aspirin to prevent PE) reported the effectiveness of the treatment ranged from 40% in the cohort with adherence of <90% to 75% in those with adherence >90% (Wright et al, 2017).…”
Section: Introductionmentioning
confidence: 99%